Adam Smith on governance and regulation: An account of his lectures on jurisprudence - Piqué, María del Pilar (2016)
The present study analyzes a little explored work of Adam Smith: his Lectures on Jurisprudence, understanding it as a "bridge" between his Moral Philosophy and his Political Economy. We show that Smith states in Theory of Moral Sentiments some tensions facing the sympathy once the bonds of affection between members of the same society began to reveal weak. This lead Smith into the study of Jurisprudence, the study of a society of strangers that need a common identification under a State that imposes rules of justice unveiled by science. In his Lectures on Jurisprudence, Smith finds that the division of labor was the result and the ultimate expression of opulence and freedom of humanity. These conduct him to answer why does the division of labor contribute to opulence and why does the division of labor brings about man's freedom and these two questions ended in the creation of The Wealth of Nations.